2022
DOI: 10.1021/acsptsci.2c00203
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Insights into the Inhibitory Mechanism of New Ebselen Derivatives against Main Protease (Mpro) of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2)

Abstract: SARS-CoV-2 main protease (M pro /3CL pro ) is a crucial target for therapeutics, which is responsible for viral polyprotein cleavage and plays a vital role in virus replication and survival. Recent studies suggest that 2-phenylbenzisoselenazol-3(2H)-one (ebselen) is a potent covalent inhibitor of M pro , which affects its enzymatic activity and virus survival. Herein, we synthesized various ebselen derivatives to understand the mechanism of M pro inhibition by ebselen. Using ebselen derivatives, we characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…7 Due to the fact that none of the known human proteases use this recognition sequence, 3CL pro has attracted considerable attention as a target for the development of inhibitors that can act as antivirals with reduced side effects. This has motivated continuous efforts to look for adequate inhibitors of the protease to be used as potential drugs, using both experimental [8][9][10][11][12][13][14] and computational approaches. [15][16][17][18][19] Many of these compounds are covalent inhibitors that contain an electrophilic site able to react with the catalytic cysteine of 3CL pro , Cys145, mimicking the behavior of the peptidic substrate.…”
Section: Introductionmentioning
confidence: 99%
“…7 Due to the fact that none of the known human proteases use this recognition sequence, 3CL pro has attracted considerable attention as a target for the development of inhibitors that can act as antivirals with reduced side effects. This has motivated continuous efforts to look for adequate inhibitors of the protease to be used as potential drugs, using both experimental [8][9][10][11][12][13][14] and computational approaches. [15][16][17][18][19] Many of these compounds are covalent inhibitors that contain an electrophilic site able to react with the catalytic cysteine of 3CL pro , Cys145, mimicking the behavior of the peptidic substrate.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, in an attempt to resolve the co-crystal structure with the protein, the authors reported that these compounds were able to transfer a hydrogenselenide unit to Cys145 through a S N Ar-like reaction taking place in the M pro active site 22 . A related study was carried out by Kumar et al, in which it was also proved the selenylation of the very same cysteine also by other benzisoselenazolones 23 . Recently, Rana et al reported a series of ebselen close analogs with anti-M pro activity, with compounds 1d and 1e being the best in class.…”
Section: Introductionmentioning
confidence: 88%
“…13 Among these, Cys145 and Cys44, located in the catalytic pocket of the enzyme, are particularly important for its function. [14][15][16] They form the catalytic dyad that cleaves the viral polyproteins into smaller functional proteins necessary for viral replication. In addition, Cys156 and Cys300 play important roles in forming enzymatically active dimeric forms of the protein.…”
Section: Several Virus-based and Host-based Targets Have Been Validatedmentioning
confidence: 99%
“…The SARS‐CoV‐2 M pro , also known as 3‐chymotrypsin‐like proteases (3CL pro ), is a canonical cysteine protease that contains 12 cysteine residues per monomer 13 . Among these, Cys145 and Cys44, located in the catalytic pocket of the enzyme, are particularly important for its function 14–16 . They form the catalytic dyad that cleaves the viral polyproteins into smaller functional proteins necessary for viral replication.…”
Section: Introductionmentioning
confidence: 99%